2018
DOI: 10.1038/s41598-018-30860-5
|View full text |Cite|
|
Sign up to set email alerts
|

Density functional theory study of the role of benzylic hydrogen atoms in the antioxidant properties of lignans

Abstract: Antioxidants are a diverse group of chemicals with proven health benefits and thus potential preventive medicine and therapeutic applications. While most of these compounds are natural products, determining their mechanism of radical scavenging and common motifs that contribute to antioxidant activity would allow the rational design of novel antioxidants. Here the origins of the antioxidant properties of ten natural products of the lignan family were studied in silico by calculating their thermochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 66 publications
2
54
0
Order By: Relevance
“…The thermochemical properties: bond dissociation energies (BDEs), ionization energies (IEs), and proton affinities (PAs) of the compounds were obtained following (RO)B3LYP/6-311++G(2df,2p)//B3LYP/6-311G(d,p) methods that are well established in the literature and best suited for thermodynamic calculations yielding data that are in good agreement with experimental values. 19,[21][22][23][24][25][26][27] Kinetic calculations were performed in the gas phase as well as in water and pentyl ethanoate solvents (the solvation model density (SMD)) by using the M05-2X/6-311++G(d,p) method and the Eyringpy code, [28][29][30][31] following the quantum mechanics based test for overall free radical scavenging activity (QM-ORSA) protocol. 30,[32][33][34][35] The conventional transition state theory and 1 M standard state at 298.15 K were applied to compute rate constant (k) according to the equation: [35][36][37][38][39][40] k ¼ sk…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermochemical properties: bond dissociation energies (BDEs), ionization energies (IEs), and proton affinities (PAs) of the compounds were obtained following (RO)B3LYP/6-311++G(2df,2p)//B3LYP/6-311G(d,p) methods that are well established in the literature and best suited for thermodynamic calculations yielding data that are in good agreement with experimental values. 19,[21][22][23][24][25][26][27] Kinetic calculations were performed in the gas phase as well as in water and pentyl ethanoate solvents (the solvation model density (SMD)) by using the M05-2X/6-311++G(d,p) method and the Eyringpy code, [28][29][30][31] following the quantum mechanics based test for overall free radical scavenging activity (QM-ORSA) protocol. 30,[32][33][34][35] The conventional transition state theory and 1 M standard state at 298.15 K were applied to compute rate constant (k) according to the equation: [35][36][37][38][39][40] k ¼ sk…”
Section: Methodsmentioning
confidence: 99%
“…No attention was paid to the effect of substitutes, such as hydroxyl, methoxyl and glucose groups in the aromatic rings, even though it is known that the presence or absence of these moieties can alter the antioxidant properties of phenolic compounds. 8,9,19 Studies of the thermodynamics and kinetics of antioxidants mainly focused on the HOOc and HOc scavenging activity, 11,15 however, the high reactivity of HOc and H-bond interactions of H-OOc with antioxidants may affect the results. 20 Larger radicals (ROOc) are also abundant in biological systems, 15 yet not much attention was paid to the activity of antioxidants against these radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the thermochemical properties: bond dissociation energies (BDEs), ionization energies (IEs), and proton affinities (PAs) of all compounds were determined in the gas phase following the well-established (RO)B3LYP/6-311++G(2df,2p)// B3LYP/6-311G(d,p) calculating model. 12,[17][18][19][20][21][22] The kinetic study in the gas phase and physiological environments, including water for polar environment and pentyl ethanoate for non-polar environment with the solvation model density (SMD), was performed according to the quantum mechanics based test for overall free radical scavenging activity (QM-ORSA) protocol 10,23,24 using the M06-2X/6-31+G(d,p) and M06-2X/6-311++G(d,p) 9,25-27 levels and the Eyringpy code. 28,29 The use of different functionals for thermochemistry and kinetics to enhance accuracy of the calculations was established and justied before.…”
Section: Methodsmentioning
confidence: 99%
“…Previous works demonstrated that quantum chemistry calculations offer an effective and elegant way to study the mechanism and kinetics of radical reactions, evaluating the antioxidant capacity of organic compounds at the molecular level in both gas phase and physiological environments. [8][9][10][11][12][13][14][15][16] Thus a thermodynamic and kinetic study in the radical scavenging activity of the natural diterpenes is crucial to glean a better understanding of their radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…The development and the assessment of methodologies for the extraction, identification, and determination of lignans are achieved [17,43,44]. Also, the “new” emerging lignans, due to LC combined with HR-MS/MS, have been, and will continue, broadening the view regarding dietary lignans [45]; simultaneously, the synthesis [46,47] and the design [48] of new compounds are being carried out.…”
Section: Introductionmentioning
confidence: 99%